Factors influencing the formation and development of the transfer potential of trade enterprises (Economics and region, 2024)
Scientific research on the factors influencing the formation and development of transfer potential in trade enterprises is extremely crucial for the contemporary business environment. It allows for a deeper understanding of the dynamics and complexities affecting success in the trade sector. Transfer potential plays a key role in ensuring the flexibility and adaptability of enterprises, which is crucial for survival amidst rapid market changes. Knowledge of these factors enables businesses to forecast future trends and adapt to them with minimal costs, enhancing the efficiency of business processes, reducing risks, and opening new development opportunities. Analyzing political, economic, social, and technological factors allows for the development of more effective management strategies. In modern conditions, the success of trade enterprises is determined by their ability to effectively adapt to changes in the business environment and develop their transfer potential. Scientifically justified, key factors of competitiveness for enterprises include the level of technological development, staff qualifications, efficiency of management processes, supply chain optimization, customer service level, innovativeness, and marketing activity. These aspects not only define opportunities but also risks for enterprises, hence comprehensive understanding and effective management enable businesses to adapt to changes, minimize risks, and maximize development opportunities. An important element is the integration of digital technologies and innovations into the business strategies of trade enterprises. This not only optimizes internal processes but also opens new avenues for interaction with customers and partners. The role of strategic planning and data analytics proves crucial in making informed decisions, assisting companies in effectively responding to changes in market conditions. Overall, flexibility, innovativeness, and customer focus determine sustainable growth and competitiveness in the contemporary business environment.
Keywords: trade enterprises; business environment; competitiveness; digital technologies; strategic planning